1999
DOI: 10.1001/archpedi.153.8.845
|View full text |Cite
|
Sign up to set email alerts
|

One-Mile Run Performance and Cardiovascular Fitness in Children

Abstract: Background: Endurance run tests are administered in schools to assess cardiovascular fitness, defined in the laboratory as maximum oxygen consumption. Objective: To examine the validity of this concept, assessing the influences of body fat and maximum values of oxygen consumption per unit time, stroke volume, heart rate, and arteriovenous oxygen difference on 1-mile (1.6km) run time in healthy sixth-grade boys. Study Design: Subjects were 36 boys with a mean (SD) age of 12.2 (0.5) years. The relationship was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 18 publications
3
13
0
Order By: Relevance
“…However, Rowland et al concluded that one-mile run performance may not serve as a strong indicator of cardiovascular fitness[66]. Drinkard et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, Rowland et al concluded that one-mile run performance may not serve as a strong indicator of cardiovascular fitness[66]. Drinkard et al .…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-six circumpubertal boys [mean age 12.2 (0.5) years] participated in a previously published study evaluating the contributions of body composition, maximal aerobic power, and cardiac output to mile run performance (Rowland et al 1999). In the present report, findings in this investigation were analyzed to determine the empirically-observed allometric relationship between _ V O 2max , body mass and mile run velocity.…”
Section: Participantsmentioning
confidence: 97%
“…There has been considerable debate over recent years as to the most appropriate method of scaling or normalizing maximum oxygen uptake ( _ V O 2max ) to remove the effects of body mass, in both adults (Astrand and Rodahl 1986;Nevill et al 1992;Nevill and Holder 1994;Nevill et al 2003) and children (Welsman et al 1996;Nevill 1997;Rowland et al 1999). The consensus of opinion suggests that to facilitate comparisons between groups of different body sizes, the most appropriate way to remove the effects of body mass (m) is to adjust _ V O 2max using the power function relationship _ V O 2max =am k , where a is known as the scaling constant and k is the body-mass scaling exponent.…”
Section: Introductionmentioning
confidence: 99%
“…Of the studies included in the review, 13 were considered high quality 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 (Tables 1 and 2), and 30 as moderate quality (Tables 3 and 4). 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 …”
Section: Resultsmentioning
confidence: 99%